Electronic and magnetic properties of Ni2MnGa: Monte-Carlo and ab-initio calculations. (August 2019) - Boughlala, A.; Benzakour, N.; Hourmatallah, A.; Bouhou, S.; Salmi, S.; Bouslykhane, K.
Abstract: This paper describes computational calculations based on the density functional theory (DFT), in order to investigate the electronic and magnetic properties of Ni2 MnGa alloys. The local density approximation (LDA) and generalized gradient approximation (GGA) methods were used, which are implemented in the MACHIKANEYAMA package designed and made by Akai [1]. As result, we found that the alloys possess a ferromagnetic behaviour with magnetic moment of 4, 07μB /cell. The analysis of the density of states (DOS) shows that the alloys have a half-metallic behaviour due to the Mn-d and Ni-d states crossing the Fermi level. Moreover, the Monte-Carlo simulation method in the framework of the Ising model gives the magnetization and the susceptibility values, respectively.